The Cross-Cultural Leadership Strategy of School Administrators under the Secondary Educational Service Area Office Bangkok 1 - Dedwongsa, Isarapong; Lapchareon, Supawadee (Community and Social Development Journal, 2023)
The objective of this survey research is to study and compare the cross-cultural leadership of school administrators under the Secondary Educational Service Area Office Bangkok 1 classified according to the academic standing, special classroom in foreign language, and school size. The sample population consisted of 357 teachers working in schools under the Secondary Educational Service Area Office Bangkok 1 during the 2022 academic year. The research instrument was a five-rating scale questionnaire. The test of accuracy found an index of item objective congruence (IOC) between 0.60-1.00 and a Cronbach’s alpha coefficient of 0.969. The statistics used in the data analysis were frequency, percentage, mean, and standard deviation. The researcher also employed a t-test technique and the one-way analysis of variance (ANOVA) technique in addition to Scheffe’s multiple comparison method. The results were that the cross-cultural leadership of school administrators under the Secondary Educational Service Area Office Bangkok 1 had an overall high-level average. When the five aspects were considered, it showed as follows: multicultural acceptance, cultural communication, equity and ethics, positive power, and organizational relationship. In addition, the teachers who differed in academic standing and school size exhibited overall differences in their opinions towards the cross-cultural leadership of school administrators at a statistical significance level of .05. However, there were no differences in the opinions of teachers who differed in special classroom in foreign language.